2020
DOI: 10.1681/asn.2020060802
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Biopsy Findings in Patients with COVID-19

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) is thought to cause kidney injury by a variety of mechanisms. To date, pathologic analyses have been limited to patient reports and autopsy series.MethodsWe evaluated biopsy samples of native and allograft kidneys from patients with COVID-19 at a single center in New York City between March and June of 2020. We also used immunohistochemistry, in situ hybridization, and electron microscopy to examine this tissue for presence of severe acute respiratory syndrome coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
479
5
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(515 citation statements)
references
References 31 publications
13
479
5
18
Order By: Relevance
“…Another finding is that some patients demonstrated collapsing focal segmental glomerulosclerosis. This pathology may be primarily limited to African American patients, and in some cases, genetic testing demonstrated the presence of APOL1 high-risk genotypes [3]. Less commonly reported findings include pigmented casts consistent with rhabdomyolysis, immune-mediated glomerular nephritis, and thrombotic microangiopathy.…”
Section: Tablementioning
confidence: 99%
“…Another finding is that some patients demonstrated collapsing focal segmental glomerulosclerosis. This pathology may be primarily limited to African American patients, and in some cases, genetic testing demonstrated the presence of APOL1 high-risk genotypes [3]. Less commonly reported findings include pigmented casts consistent with rhabdomyolysis, immune-mediated glomerular nephritis, and thrombotic microangiopathy.…”
Section: Tablementioning
confidence: 99%
“…The response to SARS-CoV-2 in humans appears to be hemophagocytic lymphohistiocytosis (HLH), characterized by immune hyperactivation that occurs when Natural Killer cells and cytotoxic T lymphocytes do not eliminate activated macrophages, leading to excessive production of pro-inflammatory cytokines 43 . These pro-inflammatory cytokines could be associated with a major pathomechanism in kidney damage causing nephrotic proteinuria, collapsing glomerulopathy, membranous glomerulopathy, nephritis, and acute tubular injury 44 . Although some data suggest the incidence of Acute Kidney Injury (AKI) by SARS-CoV-2 to be low 45,46 , other studies indicate that AKI is one of the significantly more common complications in patients who died of COVID-19, pointed out as a marker of multiple organ dysfunction and severe disease 4648 .…”
Section: Discussionmentioning
confidence: 99%
“…Although Cheng et al (1) observed high-sensitivity C-reactive protein levels to be elevated in most patients with AKI, definitive proof of the frequently invoked "cytokine storm" and its relative contribution to the majority of patients with AKI have been recently questioned. The infrequency of interstitial inflammation seen with the tubular injury subphenotype does not eliminate a potential contribution from systemic inflammation on local or regional hemodynamics (7). However, blood IL-6 levels in patients with COVID-19 have been observed to be lower compared with data from patients participating in previous National Heart, Lung and Blood Institute Acute Respiratory Distress Syndrome Network (ARDSNet) trials (8).…”
mentioning
confidence: 94%